RoCKIn Benchmarking Through Robot Competitions (IntechOpen, 2017)
The book "RoCKIn - Benchmarking Through Robot Competitions" describes the activities and achievements on the promotion of Robotics research and benchmarking in Europe through robot competitions, carried out within the framework of the RoCKIn ("Robot Competitions Kick Innovation in Cognitive Systems and Robotics") Coordination Action, a project funded by the European Commission (EC) 7th Framework Programme (FP7). RoCKIn was one of the two pioneer projects on robot competitions in Europe funded by the EC, representing the acknowledgment of robot competitions as important tools to advance research on Robotics, besides education and public awareness of Robotics. Two challenges were selected for the RoCKIn competitions due to their high relevance and impact on Europe's societal and industrial needs: domestic service robots (RoCKIn@Home) and innovative robot applications in industry (RoCKIn@Work). Along the book chapters the reader will find details on RoCKIn@Home and RoCKIn@Work, and about the activities carried out during the project lifetime, namely the developed open domain test beds for competitions targeting the two challenges and usable by researchers worldwide; the scoring and benchmarking methods to assess the performance of robot systems and subsystems; and the building up of a community of new teams. The book ends with an assessment by the project industrial partner about the impact of RoCKIn and other robot competitions on the industrial robot markets. The project work was funded by the European Commission (EC) 7th Framework Programme (FP7), under the 9th Call for projects on Information and Communication Technologies. The publishing of this book was funded by the EC FP7 Post-Grant Open Access Pilot programme.